ASSESSING THE AGRONOMIC AND ECONOMIC VIABILITY OF DISTILLERY SPENT WASH AND BOILER ASH MIXTURES AS SUSTAINABLE FERTILIZERS - Muhammad Ali Keerio; Aijaz Abbasi; Muhammad Ramzan Luhur; Ghulamullah Khaskheli (Spectrum of Engineering Sciences, 2025)
A significant by-product of the sugar industry is molasses, which distilleries utilize for alcohol production through fermentation. This process generates 10 to 15 cubic meters of wastewater for every cubic meter of alcohol produced. Common disposal methods for this waste effluent include fertilization, irrigation, composting with bio-waste, combustion, and anaerobic treatment. Rich in organic matter, mineral salts, and essential nutrients, this effluent can be efficiently repurposed as a nutrient source and soil amendment. By adopting these methods, industries can enhance soil fertility while managing waste responsibly, contributing to sustainable agricultural practices. Research studies have demonstrated that the nutrient content (NPK) in distillery sludge makes it suitable for use as a fertilizer. A developed fertilizer combining distillery spent wash (DSW) and boiler ash (BA) was tested on cotton fields, resulting in improved crop growth, higher yields, and reduced costs. This approach enhances nutrient availability and offers a viable alternative to synthetic fertilizers for agricultural productivity. A parametric study was conducted to evaluate the effectiveness of this low-cost method, focusing on the utilization of waste materials like DSW and BA from the alcohol industry as sustainable fertilizers. The findings highlight the potential of these waste-derived fertilizers to improve agricultural outcomes while addressing environmental and economic challenges, paving the way for more sustainable industrial and farming practices.